Feline vector-borne pathogens in Iran - Alireza Sazmand; Mariaelisa Carbonara; Leili Moradi; Pardis Almasi; Shiva Saruei; Mozhdeh Moradi-Jam; Anahita Akhondi; Parmida Malekzadeh; Soheila Ghaharzade-Mahabadi; Amin Bakhshani; Omid Chashnigir; Baharak Akhtardanesh; et al. (Parasites & Vectors)
Abstract Background Feline vector-borne pathogens (FeVBPs) are common in tropical and subtropical countries, mainly due to favorable climate conditions for arthropod perpetuation coupled with limited preventive measures. However, data regarding the actual burden of these infections among cats are still scarce compared with dogs. The present study aimed to provide an overview of the prevalence of FeVBPs infections in Iran. Methods From December 2018 to February 2023, a total of 848 cats of both sexes, different ages, and with outdoor lifestyle living in 7 provinces of Iran were blood sampled and molecularly screened for Hepatozoon spp., Babesia spp., Cytauxzoon spp., Dirofilaria spp., and Leishmania spp. Results Overall, 5.4% of cats scored positive for at least one VBP, with Hepatozoon spp. being the most common (3.8%), followed by Leishmania spp. (2.5%) and Dirofilaria immitis (0.7%). The Hepatozoon-positive cats lived in localities from the eastern, western, and central-northern regions; most of them (n = 25) were infected by Hepatozoon felis, and the remaining (n = 3) by Hepatozoon canis. Leishmania spp.-infected cats were detected from the east, center, and west of the country, while D. immitis-positive animals lived in central-north areas. Conclusions To our knowledge, this is the first large-scale molecular epidemiology study of vector-borne pathogens in cats in Iran. The circulation of several VBPs, including those with zoonotic potential (i.e., D. immitis and Leishmania spp.) highlights the importance of endo- and ectoparasite control measures in owned cats and suggests that controlling the population of feral animals (e.g., through spaying and neutering campaigns) would contribute to reducing the risk of transmission of VBPs. Graphical abstract